Study of Oxidative Stress in Relation with Antioxidant Status in Chronic Bronchitis - Raut, Anita Madhav; Suryakar, A.N.; Mhaisekar, Dilip (International Journal of Public Health Science (IJPHS), 2012)
Lipid peroxide plays an important role in inflammatory lung diseases. Increased epithelial permeability produced by cigarette smoke is likely to be mediated though depletion of the Total Antioxidant Capacity .Oxidative stress has been recognized as a central feature of smoke induced chronic bronchitis. Imbalance between oxidants and Total Anioxidant Capacity is also an established fact in these patients. 60 patients with chronic bronchitis included in the study. Their base line clinical examination, malondialdehyde (MDA), nitric oxide, alpha tochopherol and Total Antioxidant Capacity were measured. 100 healthy non-smokers’ were served as controls. The mean malondialdehyde levels and nitric oxide in the patients at base line were higher than Controls (p<0.001). Plasma alpha-tocopherol and total antioxidant capacity were lower (p<0.001) in the patients compared to controls. The present study shows that initially the plasma lipid peroxide (MDA) levels were high and antioxidants. (alpha- tocopherol, total antioxidant capacity) were low in patients with chronic bronchitis. Our results suggest the presence of oxidative stress and decrease in total antioxidant capacity in chronic bronchitis.DOI: http://dx.doi.org/10.11591/ijphs.v1i1.523